Exploring the appearance of and messaging on antibiotics to address inappropriate antibiotic use - public and pharmacists views. (30th November 2022) - Hawksworth, G; Akhtar, A; Fitzgerald, K; Shah, A; Xie, V; AlDeyab, M; Frank, S; Howard, P
Abstract: Introduction: The purpose of medicines labelling and packaging is to provide clear unambiguous identification of the medicine and the conditions for its safe use, allowing patients to understand and act on the information. 1 Inappropriate antibiotic usage, (deviation from directions provided to the patients by the prescriber, resulting in sub-optimal treatment) may result in exposing bacteria to sub-therapeutic plasma concentrations and/or environment, which are one of the main drivers of Antibiotic Resistance. 2 A recent comprehensive analysis showed the global burden associated with drug-resistant infections in 2019 was an estimated 4.95 million deaths. 3 Aim: To ascertain the support from pharmacists and the public and their perceptions on the likely barriers to harmonising or standardising physical appearance and/or messaging on antibiotic packaging to reduce inappropriate antibiotic usage. Methods: This study received ethics approval from the University of Huddersfield. In partnership with NHS England Antimicrobial Stewardship lead for North-East and Yorkshire, two questionnaires (public and pharmacist) were piloted. The final version was transferred to Qualtrics (online questionnaire format). During a 5-week period public questionnaires were distributed via posters with QR codes and social media. Pharmacist questionnaires were emailed to consenting pharmacists (community, hospital, GP practice, industry) around Huddersfield, Doncaster, Rochdale, Dewsbury and Leeds. The data underwent descriptive statistical analysis. Results: Inappropriate antibiotic usage (saving for future use) was admitted by 23.5% of the 174 public participants, sharing with others (2.5%), throwing their antibiotics in the bin (32.7%) and other inappropriate usage was reported. This compared to 22.2% returning antibiotics to the pharmacy for disposal. 100% of pharmacists (40) think inappropriate antibiotic use needs to be addressed; the majority of pharmacists (55.5%) and the public (61.4%) think a harmonised antibiotic appearance would reduce inappropriate use. 'Putting the word "ANTIBIOTICS" on the packaging would improve antibiotic packaging appearance' was the top improvement selected by pharmacists (38.3%) and public (35.3%). Pharmacists (38.9%) thought antibiotic manufacturers would be the greatest obstacle to harmonised packaging. The majority of public (70.5%) and pharmacists (85.3%) think a standardised messaging system would help reduce inappropriate antibiotic use. Both pharmacists (41.1%) and public (47%) highlighted that a standard leaflet for appropriate use could improve antibiotic use. Pharmacists (47.8%) thought that multiple stakeholders (e.g., MHRA, manufacturers, etc) would be the barriers to a standardised messaging. Discussion/Conclusion: Inappropriate antibiotic use by individuals who re-use leftovers or share their antibiotics may result in a treatment failure and could to increase AMR. Improvements in antibiotic packaging and patient information leaflets with appropriate disposal instructions could help minimise AMR. Limitations of this study include the low number of practice and industrial pharmacist respondents compared to community and hospital pharmacists. Public and pharmacist respondents supported the wording "ANTIBIOTIC" on antibiotic packaging and a standardised leaflet covering increasing adherence and appropriate disposal of leftovers. This study warrants further evaluation with regulators, manufacturers and other key stakeholders. References: 1. HM Government. Best practice guidance on the labelling and packaging of medicines. Available from: https://www.gov.uk/government/publications/best-practice-in-the-labelling-and-packaging-of-medicines (Accessed: 10/09/22). 2. Gullberg, E., et al. Selection of resistant bacteria at very low antibiotic concentrations. PLoS Pathogens, 2011;7(7):e1002158. https://doi.org/10.1371/journal.ppat.1002158 3. Antimicrobial Resistance Collaborators. Global burden of bacterial antimicrobial resistance in 2019: a systematic analysis. Lancet 2022. https://doi.org/10.1016/S0140-6736(21)02724-0 .